Clinical efficacy of 60-mg dexlansoprazole and 40-mg esomeprazole after 24 weeks for the on-demand treatment of gastroesophageal reflux disease grades A and B: a prospective randomized trial - Chiang HH; Wu DC; Hsu PI; Kuo CH; Tai WC; Yang SC; Wu KL; Yao CC; Tsai CE; Liang CM; Wang YK; Wang JW; et al. (Dove Medical Press, 2019)
Hung-Hsien Chiang,1 Deng-Chyang Wu,2 Pin-I Hsu,3 Chao-Hung Kuo,2 Wei-Chen Tai,1 Shih-Cheng Yang,1 Keng-Liang Wu,1 Chih-Chien Yao,1 Cheng-En Tsai,1 Chih-Ming Liang,1 Yao-Kuang Wang,2 Jiunn-Wei Wang,2 Chih-Fang Huang,4 Seng-Kee Chuah,1  on behalf of the Taiwan Acid-Related Disease Study Group 1Division of Hepato-Gastroenterology, Department of Internal Medicine, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, Taiwan; 2Division of Gastroenterology, Department of Internal Medicine, Kaohsiung Medical University Hospital and Kaohsiung Medical University, Kaohsiung, Taiwan; 3Division of Gastroenterology, Department of Internal Medicine, Kaohsiung Veterans General Hospital, National Yang-Ming University, Kaohsiung, Taiwan; 4Division of Family Physicians, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, TaiwanPurpose: Research comparing the clinical efficacy of dexlansoprazole and esomeprazole has been limited. This study aims to compare the clinical efficacy of single doses of dexlansoprazole (modified-release 60 mg) and esomeprazole (40 mg) after 24-week follow-up in patients with mild erosive esophagitis.Methods: We enrolled 86 adult GERD subjects, randomized in a 1:1 ratio to two sequence groups defining the order in which they received single doses of dexlansoprazole (n=43) and esomeprazole (n=43) for 8 weeks as initial treatment. Patients displaying complete symptom resolution (CSR) by the end of initial treatment (8 weeks) were switched to on-demand therapy until the end of 24 weeks. Follow-up endoscopy was performed either at the end of 24 weeks or when severe reflux symptoms occurred. Five patients were lost to follow-up, leaving 81 patients (dexlansoprazole, n=41; esomeprazole, n=40) in the per-protocol analysis.Results: The GERDQ scores at 4-, 8-, 12-, 16-, 20-, and 24-week posttreatment were less than the baseline score. The CSR, rate of symptom relapse, days to symptom resolution, sustained healing rate of erosive esophagitis, treatment failure rate, and the number of tablets taken in 24 weeks were similar in both groups. The esomeprazole group had more days with reflux symptoms than the dexlansoprazole group (37.3±37.8 vs 53.9±54.2; P=0.008). In the dexlansoprazole group, patients exhibited persistent improvement in the GERDQ score during the on-demand period (week 8 vs week 24; P<0.001) but not in the esomeprazole group (week 8 vs week 24; P=0.846).Conclusions: This study suggests that the symptom relief effect for GERD after 24 weeks was similar for dexlansoprazole and esomeprazole. Dexlansoprazole exhibited fewer days with reflux symptoms in the 24-week study period, with better persistent improvement in the GERDQ score in the on-demand period.(ClinicalTrials. gov number: NCT03128736)Keywords: dexlansoprazole, esomeprazole, 24-week response, gastroesophageal reflux disease, on-demand, GERDQ score